Produzindo olhares sobre a sexualidade referenciada ao lgbtqiap+ no cenário de uma escola estadual no ensino médio - Bispo, Margarida Maria Araujo (2024)
In the educational context that encompasses Basic Education, addressing the concept of gender and sexuality aimed to understand how LGBTQIAP+ people show their experiences in the daily life of a high school in the city of Tobias Barreto/Sergipe. Thus, this research had as its general objective to reveal the social representations, the knowledge constructed and the strategies mobilized by teachers in a high school in Tobias Barreto/SE, in relation to gender diversity, referenced in the sexualized body of LGBTQIAP+ students in the expansion of rights and construction of citizenship. The active methodology used in this research has a proposal based on the feminist, post-structuralist and queer perspective, aiming to unveil the sociabilities of LGBTQIAP+ groups in the daily life of high school in public schools. The production of knowledge about the object has as its perspective a qualitative research, through the following sources: A) Participant observation; B) Field diary; C) Literary Workshop; D) Focus Group. The methodological framework for the analysis of symbolic forms is aligned with in-depth hermeneutics for the interpretation of forms of representations circulating about the object, including in the adopted homoerotic literature texts. This methodological option allowed for Socio-historical Analysis, Formal or Discursive Analysis and Interpretation/Reinterpretation, articulated with other methods of analysis and strategies of symbolic construction, immersed and produced amidst power relations, existing in High School at the school where the research was conducted. Through this finding, it became clear that the main problems that permeate the lives of LGBTQIAP+ people in schools, observed through the general results verified in the focus groups, workshops and sorority activities, were: veiled homophobia and aggressive homophobia, naturalization of prejudice and homophobia as a cultural factor in schools.